Gas detection technology for thermal runaway of lithium-ion batteries - Qian, Yihua; Zhao, Yaohong; Li, Zhi; Wang, Qing; Zhao, Yifeng (Frontiers in Physics, 2025)
This paper presents a comprehensive review of gas detection and early warning technologies for lithium‐ion battery thermal runaway a critical safety concern in modern energy storage and electric vehicle applications. With the increasing push for higher battery energy densities, thermal runaway has emerged as a severe risk characterized by rapid self-heating, complex exothermic reactions, and the evolution of flammable gases that can lead to explosions and fires. The review begins by detailing the underlying physicochemical mechanisms of thermal runaway and the subsequent gas generation processes, emphasizing the early evolution of gas signals as a promising indicator for imminent failure. A wide range of detection techniques are critically evaluated, including gas chromatography, Fourier-transform infrared spectroscopy, Raman spectroscopy, differential electrochemical mass spectrometry, metal oxide semiconductor sensors, and non-dispersive infrared technology—each offering unique advantages and facing distinct challenges in practical applications. Special attention is given to the emerging role of optical fiber-based sensors (e.g., Fabry–Perot interferometers, fiber Bragg gratings, and fluorescence-based sensors), which provide notable benefits such as immunity to electromagnetic interference, flexible integration, and high sensitivity for key gases (CO2, H2, and CH4). The paper concludes by discussing the limitations of current approaches and proposes future directions to achieve integrated, cost-effective, and robust battery safety monitoring systems.